PREMI ASURANSI JIWA CONTINGENT DENGAN HUKUM DE MOIVRE - Elni Tristianti; Hasriati '; Rolan Pane (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
This article discusses annual premium of contingent insurance using De Moivre law. Contingent insurance is those where the payment cash compensation is based on the sequence of death. Contingent insurance also uses compound contingent functions affected by the order of probability delay of death. In this article, we discusses only for two cases. Annual premium calculation contingent insurance is obtained by prior determining the single premium and the annuity based on De Moivre law.